ANALISIS PERBANDINGAN DEBT TO EQUITY RATIO ANTARA PT KALBE FARMA TBK DAN PT KIMIA FARMA TBK - Mujabir; Aliyah Pratiwi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This study aims to analyze whether or not there is a difference in Debt to Equity Ratio between PT Kalbe Farma Tbk and PT Kimia Farma Tbk. This type of research used in this research is comparative research (comparison). Comparative research is used to determine the ratio of Debt to Equity Ratio between PT Kalbe Farma Tbk (X1) and PT Kimia Farma Tbk (X2). The variable in this study is DER (Debt to Equit Ratio). The sampling method used is the purposive sampling method, which is taking the sample previously determined based on the aims and objectives of the research and the sample in this study is the financial statements of PT Kalbe Farma Tbk and PT Kimia Farma Tbk for 5 years starting from 2015 to 2019. Analysis of the data used in the form of two independent samples t-test. The results of the analysis show that there is a difference in Debt to Equity Ratio between PT Kalbe Farma Tbk and PT Kimia Farma Tbk, the results of data interpretation can compare the value tcount and ttable. If t_count ≥ t_table, then H0 is rejected and Ha is accepted. So (5,755) ≥ (2,306), then H0 is accepted and Ha is rejected.